2001
DOI: 10.1107/s0108270101018273
|View full text |Cite
|
Sign up to set email alerts
|

4-[3-(3,4-Dimethoxyphenyl)prop-2-enoyl]phenyl methacrylate and 4-[3-(2-bromophenyl)prop-2-enoyl]phenyl methacrylate

Abstract: Chalcones (,-unsaturated ketones) are effective antitumour agents. It has been proved that having halogen or methoxy groups substituted in various positions of the phenyl ring enhances the activity of chalcones many times. The title compounds, C 21 H 20 O 5 and C 19 H 15 BrO 3 , respectively, were chosen for crystallographic study in order to determine their structures and conformations. In both compounds, the keto group is in the s-cis conformation and is almost planar. There are weak intramolecular interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
4
1
0
Order By: Relevance
“…The molecule is slightly twisted, the dihedral angle between the two aromatic rings being 9.51 (7) . The bond lengths and angles are comparable with those reported for related structures (Raj et al, 1996;Shanmuga Sundara Raj et al, 1997;Jeyabharathi et al, 2002;Ravishankar et al, 2003;Thamarai Selvi et al, 2003).…”
Section: Commentsupporting
confidence: 87%
“…The molecule is slightly twisted, the dihedral angle between the two aromatic rings being 9.51 (7) . The bond lengths and angles are comparable with those reported for related structures (Raj et al, 1996;Shanmuga Sundara Raj et al, 1997;Jeyabharathi et al, 2002;Ravishankar et al, 2003;Thamarai Selvi et al, 2003).…”
Section: Commentsupporting
confidence: 87%
“…The bond lengths and angles are within normal ranges (Allen et al, 1987) and similar to those observed in other comparable structures (Jeyabharathi et al, 2002;Patil et al, 2006;Ravishankar et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Radhika et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Santhi et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Selvam et al, 2005;Sathiya Moorthi, Chinnakali, Nanjundan, Unnithan et al, 2005;Teh et al, 2006). The short H5Á Á ÁH8 (2.28 Å ) contact causes the bond angle C9-C10-C11 [123.08 (9) ] to deviate significantly from 120 .…”
Section: Commentsupporting
confidence: 83%
“…Bond lengths and angles in the central enone unit agree with those found in chalcone derivatives with different para substituents (Jeyabharathi et al, 2002;Rabinovich & Shakked, 1974). Bond lengths and angles in the central enone unit agree with those found in chalcone derivatives with different para substituents (Jeyabharathi et al, 2002;Rabinovich & Shakked, 1974).…”
Section: Commentsupporting
confidence: 76%